ON THE RELATIONSHIP BETWEEN A HOT-CHANNEL-LIKE SOLAR MAGNETIC FLUX ROPE AND ITS EMBEDDED PROMINENCE - Cheng, X.; Ding, M. D.; Srivastava, A. K.; and et. al. (Institute of Physics Publishing, 2014)
A magnetic flux rope (MFR) is a coherent and helical magnetic field structure that has recently been found likely to appear as an elongated hot channel prior to a solar eruption. In this Letter, we investigate the relationship between the hot channel and the associated prominence through analysis of a limb event on 2011 September 12. In the early rise phase, the hot channel was initially cospatial with the prominence. It then quickly expanded, resulting in a separation of the top of the hot channel from that of the prominence. Meanwhile, they both experienced an instantaneous morphology transformation from a Λ shape to a reversed-Y shape and the top of these two structures showed an exponential increase in height. These features are a good indication of the occurrence of kink instability. Moreover, the onset of kink instability is found to coincide in time with the impulsive enhancement of flare emission underneath the hot channel, suggesting that ideal kink instability likely also plays an important role in triggering fast flare reconnection besides initiating the impulsive acceleration of the hot channel and distorting its morphology. We conclude that the hot channel is most likely the MFR system and the prominence only corresponds to the cool materials that are collected in the bottom of the helical field lines of the MFR against gravity.
Keywords: Sun: corona; Sun: coronal mass ejections (CMEs); Sun: filaments, prominences; Sun: magnetic fields